Synergistic effect of graphene enhances the responsivity of hybrid perovskite photodetector - Chu, Jingyu; Liu, Zirui; Liu, Peiding; Xie, Jiyang; Xiang, Jinzhong; Qiu, Feng (Cell reports physical science, 2024)
Organometal halide perovskite has aroused extensive interest due to its high absorption coefficient and flexible synthetic strategy for fabricating sensitive and low-cost photodetectors. Nevertheless, obtaining large and ordered orientation perovskite grain, developing enhanced optical absorption, and restraining defect states of grain boundaries are still open and challenging processes. Here, we report a flexible hierarchical architecture to promote grain growth and absorption strength. Therein, graphene and its derivatives are adopted to produce enlarged grain via an in situ hot-casting scheme. The surface plasmon resonance effect of highly conductive reduced graphene oxide-silver (Ag-rGO) nanoparticles is introduced to improve perovskite absorbance, enhancing responsivity by nearly four orders of magnitude to 13 AW−1. Meanwhile, density functional theory calculations and finite-difference time-domain analysis confirm the absorption enhancement and effective separation of the photogenerated carriers. This work elucidates the synergistic effect of graphene based on strain template and surface plasmon resonance in fabricating high-responsivity photodetectors. [Display omitted] •MAPbI3 perovskite films via an in situ hot-casting scheme•Synergistic effect of graphene enhances the absorbance of MAPbI3•Surface plasma resonance effect enhances the photodetectors’ responsivity•DFT calculation and FDTD analysis confirm the enhancement Chu et al. prepare large-area graphene and synthesize Ag-rGO to fabricate a MAPbI3 photodetector. The synergistic effect of graphene is proven to enlarge the grain size of MAPbI3 film and enhance the absorbance. DFT calculations and FDTD solutions also endorse the absorption enhancement of the perovskite layer and the synergistic effect.